2024
DOI: 10.3233/nre-230382
|View full text |Cite
|
Sign up to set email alerts
|

Long-term impact of a community-based adapted boxing program on physical functioning and quality of life of individuals with Parkinson’s disease

Félix-Antoine Savoie,
Simon Benoit,
Eléonor Riesco
et al.

Abstract: BACKGROUND: Adapted boxing can help improve the physical functioning and health-related quality of life (HRQoL) of individuals with Parkinson’s disease (PD). Whether these benefits persist longitudinally is unclear. OBJECTIVE: The purpose of this retrospective study was to evaluate the impact of a community-based adapted boxing program on the physical functioning and HRQoL of individuals with PD over 1–1.5 years. METHODS: Twenty-six individuals with PD agreed to share their results on tests administered upon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Preliminary non-randomized controlled studies have highlighted the positive effect of boxing programs on the balance [29,30], mobility [31][32][33], and quality of life [34,35] of people with Parkinson's disease. PD patients who attended boxing programs during the study period reported an improvement in fatigue levels as they felt more energetic, experienced a reduced fear of falling, anxiety, depression, and improved their social lives [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary non-randomized controlled studies have highlighted the positive effect of boxing programs on the balance [29,30], mobility [31][32][33], and quality of life [34,35] of people with Parkinson's disease. PD patients who attended boxing programs during the study period reported an improvement in fatigue levels as they felt more energetic, experienced a reduced fear of falling, anxiety, depression, and improved their social lives [36,37].…”
Section: Introductionmentioning
confidence: 99%